The Strategic Role of Green Libraries in Sustainable Development: Evidence from International Award-Winning Projects - Kişi, Nermin (Information World, 2025)
The aim of this study is to examine the impact of green libraries on sustainable development. In this regard, the study focuses on projects awarded the “Best Large-Scale Green Library” prize by the International Federation of Library Associations and Institutions (IFLA) in 2024, evaluating their potential contributions to the Sustainable Development Goals (SDGs). In this qualitative research design, the websites of the award-winning libraries and reports on the projects were analyzed through content analysis. The projects were comprehensively evaluated in terms of environmental, social, and economic sustainability. The findings indicate that green libraries not only serve as centers for information access but also assume a strategic role in fostering environmental awareness, supporting social development, and generating economic benefits. The theoretical contribution of the study lies in offering a new perspective to the literature by systematically examining the relationship between green libraries and the SDGs. Its practical contribution lies in providing a multi-dimensional evaluation of internationally award-winning green library projects from a sustainability standpoint, thereby offering concrete recommendations for the more effective and comprehensive implementation of future projects.